Novel loss-of-function variants in WDR26 cause Skraban-Deardorff syndrome in two Chinese patients - Yang, Qi; Zhou, Xunzhao; Yi, Sheng; Li, XiaoLing; Zhang, Qiang; Zhang, Shujie; Lin, Li; Yi, Shang; Chen, Biyan; Qin, Zailong; Luo, Jingsi (Frontiers in Pediatrics, 2024)
Mutations in the protein WD repeat structural domain 26 (WDR26, MIM 617424) have been identified as the cause of autosomal dominant Skraban-Deardorff syndrome, a rare genetic disorder characterized by intellectual disability (ID), developmental delay (DD), hypotonia, epilepsy, infant feeding difficulties, gait abnormalities and distinctive facial features. The objective of this study is to investigate the genetic factors that may contribute to the development of Skraban-Deardorff syndrome in affected individuals.In this study, we used whole-exome sequencing (WES) to analyze pathogenic and likely pathogenic variants in two unrelated Chinese patients with DD and ID. We confirmed the origin of the variants by conducting Sanger sequencing and classified them according to ACMG/AMP guidelines.Here, two novel de novo variants (c.1797delC(p.His599fs*11) and c.1414C>T(p.Gln472*)) in the WDR26 gene have been identified in two Chinese patients with Skraban-Deardorff syndrome. These patients exhibit a range of symptoms, including varying degrees of ID, DD, speech delay, an abnormal wide-foot and/or stiff-legged gait, facial dysmorphism, behavioural abnormalities, with or without seizures.In this study, We report two unrelated Chinese patients with Skraban-Deardorff syndrome caused by novel de novo pathogenic variants of the WDR26 gene. These patients showed a clinical phenotype similar to that of patients with the WDR26 variant. Compared to reported cases with WDR26 pathogenic variants, patient 2 presented a novel complication of severe behavioural problems, including hyperactivity, social anxiety, self-mutilation, impulsivity and violent behaviour. This research broadens the range of genetic and clinical features of Skraban-Deardorff syndrome. In addition, the symptoms may become more pronounced as the patient ages. Furthermore, our report highlights the clinical diversity of Skraban-Deardorff syndrome. The findings may assist healthcare professionals in providing more accurate genetic testing and counselling to affected families and improving the overall management of the condition.